The Effects Of Environment Risk, Capital Structure, and Corporate Strategy on Assets Productivity, Financial Performance and Corporate Value: a Study on Go Public Companies Registered at Jakarta Stock Exchange - Chandra, Teddy (The International Journal of Accounting and Business Society, 2010)
This study was aimed at: (1) examining the effects of environment risk consisted oi financial risk, business risk and market risk on corporate strategy, capital structure, asset productivity, financial performance and corporate value. (2) examining the effects of corporate strategy consisted of liquidity, sales growth, assets growth and growth potential on capital structure, assets productivity, financial performance and corporate value. (3) examining capital on assets productivity, financial performance and corporate value. The research was an explanatory study. This study was an explanatory research. All companies registered in Jakarta Stock Exchange in 2000-2004 periods were used as samples. They were divided into main board category consisted of 71 emitters, development board 62 emitters, and total board 134 emitters. Structural Equation Model was used as analysis method. SPSS 11.5 and AMOS 5.0 were used for processing data and allowing hypothetical tests to be performed. The results indicated that: (1) investors expect main board companies to adopt free cash flow whereas development board companies were expected to be more conservative by adopting pecking order theory. Most Indonesian companies were expected to adopt the latter. And, in fact, most of main, development, and total board companies in Indonesia tend to adopt pecking order theory. (2) In general, the increase of company's value was influenced by the increase of corporate strategy and capital deduction, but the increase would be much more higher if accompanied by raising assets productivity. For development board companies in particular, the increase of company's value should be accompanied by company's financial performance. (3) Creditors do not consider company's financial risk in giving loans, this implies the increase of stacked credit. (4) Investors do not trust company's financial performance report. (5) Strategic management may provide help in explaining capital structure phenomena with significant influence of corporate strategy on both capital structure and company's value. Key Words: Corporate Strategy, Environment Risk, Capital Structure, Assets Productivity, Financial Performance, Company's Value, financial risk, business risk market risk, sales growth, assets growth, growth potential, liquidity, debt to equity ratio, debt to assets ratio, equity to Assets ratio, return to assets ratio, basic earning ratio, pecking order Theory, free cash flow theory.